2020
DOI: 10.1093/eurpub/ckaa208
|View full text |Cite
|
Sign up to set email alerts
|

Sleep pattern in the US and 16 European countries during the COVID-19 outbreak using crowdsourced smartphone data

Abstract: Background To stop the spread of the new coronavirus disease in 2019 (COVID-19), many countries had completely locked down. This lockdown restricted the everyday life of the affected residents and changed their mobility pattern, but its effects on sleep pattern were largely unknown. Methods Here, utilizing one of the largest crowdsourced database (Sleep as Android), we analyzed the sleep pattern of 25 217 users with 1 352 513… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
6
26
0
Order By: Relevance
“…It is possible that older adults interested in lifestyle behaviors and/or mental wellbeing during COVID-19 lockdowns could be more prone to participate and to perceive differences between pre- and during COVID-19 lockdowns. Thirdly, PA levels measurements were based on subjective descriptions rather than objective assessment, which could contribute to an overestimation of the self-reported PA levels [ 94 ]. Though, Tran et al [ 95 ] showed that IPAQ-SF is an acceptable tool to assess PA in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that older adults interested in lifestyle behaviors and/or mental wellbeing during COVID-19 lockdowns could be more prone to participate and to perceive differences between pre- and during COVID-19 lockdowns. Thirdly, PA levels measurements were based on subjective descriptions rather than objective assessment, which could contribute to an overestimation of the self-reported PA levels [ 94 ]. Though, Tran et al [ 95 ] showed that IPAQ-SF is an acceptable tool to assess PA in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported shorter nocturnal TIB independent of insomnia, no change in TIB, or improved sleep quality [ 15 21 ]. Studies accessing large scale databases from wearable [ 22 ] or smartphone crowdsourcing technology [ 23 , 24 ] report that at the population level, sleep was ~20 minutes later and ~20 minutes longer during social-distancing. Only one study to our knowledge collected TIB data prospectively from young adult university students, using a daily log to record bedtime and wakeup time for a week prior to and again during public ’Stay-At-Home’ orders [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, highly consistent lockdown-related lifestyle changes have been documented across different populations and countries 5,[53][54][55] . Prior studies in Singapore confirm these lockdown effects in wider samples of working adults and children 12,56 .…”
Section: Discussionmentioning
confidence: 99%